Financial Freedom or Financial Chaos? The Rise of Defi Platforms - Radha Thangarajan, Samisha B, Vinay M, Nagarajeswari M, Jayalakshmi J P, (European Economic Letters (EEL), 2024)
Decentralized Finance (DeFi) platforms are transforming traditional financial systems by offering open, permissionless access to services such as lending, borrowing, trading, and investing through blockchain technology. By removing intermediaries and using smart contracts, DeFi democratizes finance, potentially addressing financial exclusion in underserved regions. While DeFi presents opportunities for financial inclusion and innovation, it also introduces significant risks. Technical vulnerabilities, such as smart contract hacks, can compromise the system. Financial risks include liquidity shortages, market volatility, and systemic instability. Additionally, the anonymity and decentralization of DeFi create loopholes for illicit activities like money laundering and fraud, posing challenges for regulatory and law enforcement agencies. Regulating DeFi is complex, as traditional financial regulations often do not align with decentralized ecosystems. This paper examines regulatory approaches across different jurisdictions and highlights issues such as assigning legal responsibility, protecting consumer interests, and combating financial crimes while preserving innovation. Regulatory arbitrage, where DeFi platforms shift to regions with lax oversight, further complicates global regulation. The paper concludes that DeFi’s success depends on mitigating risks and establishing a balanced regulatory framework that fosters innovation while ensuring financial stability and consumer protection. Future research should focus on developing risk assessment models and regulatory strategies tailored to the decentralized finance landscape.